World Music Pedagogy: the presentation of a multicultural approach of music education (Revista NUPEART, 2024)
This article focuses on the multicultural music teaching proposal known as world music pedagogy or simply world music, presenting its philosophy and history, as well as some of its possibilities and limitations for the Brazilian context, through a critical analysis. To this end, a document analysis was carried out (SOUZA; GIACOMONI, 2021) in different documents that help in the process of understanding the historical context of the development of world music pedagogy. After that, a bibliographical review was carried out (RANDOLPH, 2007) on articles published in journals classified in the upper strata of the CAPES evaluation, between 2000 and 2020 that have world music pedagogy as a theoretical reference or central focus, which allowed an overview of the philosophical and methodological basis of this approach, which lacks a greater depth in the Brazilian context.
Keywords: Multiculturalism; World Music Pedagogy; Music Education